Anticancer properties of recipes derived from nigeria and african medicinal plants on breast cancer cells in vitro - Mutiu A. Alabi; Annamalai Muthusamy; Shama P. Kabekkodu; Olugbenga O. Adebawo; Kapaettu Satyamoorthy (Scientific African, 2020)
The study was carried out to examine the effects of two recipes prepared from Nigerian and African medicinal plants on the cell cytotoxicity, cell cycle distribution and apoptosis on breast cancer (MCF-7 and MDA-MB-231) cells and normal human fibroblasts. In vitro cytotoxicity and anti-proliferative effect was evaluated by 3-[4, 5-dimethylthizol-2-yl]-2, 5-diphenyltetrazolium bromide (MTT) assay while cell cycle and apoptosis were evaluated by flow cytometry using propidium iodide (PI) staining. The reactive oxygen species analysis by DCFDA staining and flow cytometry analysis while alterations in Mitochondrial Membrane Potential (MMP, ∆Ψm) were determined by staining the cells with Rhodamine 123 then FACS Calibur flow-cytometry analysis. Expression of apoptotic-related proteins and key signalling transduction proteins was carried out by western blotting. MTT assay results indicated that the recipes were able to inhibit the growth and proliferation of cancer cells and fibroblasts in a dose-dependent manner (P < 0.05). Nevertheless, both recipes exhibited G0/G1 cell cycle arrest by flow cytometry. The reactive oxygen species analysis showed that the extracts did not induce free radical generation in the cancer cells whereas the ∆Ψm assessment showed alterations in mitochondrial membrane potential with increased expression of two apoptosis inducing protein i.e. caspase-3 and poly (ADP-ribose) polymerase. The two recipes inhibited cell proliferation through the induction of G0/G1 cell cycle arrest and increased expression of apoptotic inducing protein, which leads to cancer cell death. This study provides an early evidence to support the traditional use of African medicinal plant recipes in cancer treatment.